2009
DOI: 10.4067/s0718-58392009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compost Application on Some Properties of a Volcanic Soil from Central South Chile

Abstract: Soil compost application is a common soil management practice used by small farmers of Central-South Chile that produces positive effects on soil properties and also promotes presence and activity of arbuscular mycorrhizal fungi (AMF). This fungi form symbiosis with plant roots improving plant nutrition, as well as producing glomalin, a glycoprotein that has been associated with soil aggregation stability. Therefore, the aim of this study was to evaluate, in an Ultisol from Central-South Chile, the effect of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 52 publications
6
44
0
5
Order By: Relevance
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Formation of complex Alhumic substance leads to lower hydrogen production from Al hydrolysis in soil, thereafter increasing soil pH. Previous studies pointed out that application of organic fertilizer raised soil pH Valarini et al 2009). In addition, Udepts had greatest soil pH followed by Andepts and Udults.…”
Section: Effect Of Water Hyacinth Compost On Soil Qualitymentioning
confidence: 99%
“…Although, the added effects of organic fertilizers at the beginning was low but with time it started to improve soil properties. The gradual effects of organic fertilizers reached through improved physical properties and enhancement of microorganism of the soil (Valarini et al, 2009;Ding et al, 2013;Pane et al, 2015). This reflects their importance of use in arid soils which were characterized by poor physical properties and lacking of microorganisms.…”
Section: Diameter Growth (Dg) and Relative Monthly Diameter Incrementmentioning
confidence: 99%
“…It is also, important for mitigating N 2 O emissions from the soils (Ding et al, 2013), enhances bio-stimulation, which increases soil microorganisms (Valarini et al, 2009) and increases nutrient uptake (Pane et al, 2015). The use of organic fertilizers leads to increased seed yield and seed quality contents in many plants (Jahan et al, 2008;Piraveena and Seran, 2010;Seran and Suthamathy, 2013).…”
Section: Introductionmentioning
confidence: 99%